SPE/DOE Symposium on Improved Oil Recovery 2006
DOI: 10.2118/99678-ms
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Two-Phase Immiscible Pulsed Flow

Abstract: Cyclic waterflooding has received recent attention since many studies and field tests have shown that it may lead to additional oil recovery at virtually zero additional cost. Even though the process is in principle very similar to conventional waterflooding, there are interesting new effects taking place under the pulsed conditions that need to be properly quantified for a realistic field deployment of the cyclic injection process. Two-phase immiscible pulsed flow experiments performed on ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…This also indicates that, to achieve a relatively stable displacement in CO 2 miscible flooding, the fast oscillation of displacement rates with short periods should be used. This finding is similar to the experimental results in waterflooding by Ivanov and Araujo (2006) and the Vapex process by Muhamad et al (2012), in which the shortest cyclic periods lead to the highest oil recovery. However, the mechanisms are different because of the nature of the different displacements.…”
Section: Cyclic Displacementssupporting
confidence: 90%
See 1 more Smart Citation
“…This also indicates that, to achieve a relatively stable displacement in CO 2 miscible flooding, the fast oscillation of displacement rates with short periods should be used. This finding is similar to the experimental results in waterflooding by Ivanov and Araujo (2006) and the Vapex process by Muhamad et al (2012), in which the shortest cyclic periods lead to the highest oil recovery. However, the mechanisms are different because of the nature of the different displacements.…”
Section: Cyclic Displacementssupporting
confidence: 90%
“…Results indicated that the pulsed tests could increase the oil recovery rates and final sweep efficiency by 10% over non-pulsed tests. Ivanov and Araujo (2006) carried out an experimental study on immiscible pulsed flow in waterflooding. Several parameters were examined, including bead size, cycle period, injection rate and oil viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…We used this approach because it was not possible to continuously change bottom hole pressure in the wells in the simulator to mimic the synthetic tidal variations. This method has been previously used by Ivanov and Araujo (2006).…”
Section: Numerical Simulationmentioning
confidence: 99%